2020
DOI: 10.1021/acs.joc.0c00689
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Potential of Zerumbone to Generate a Library with Six Natural Product-like Skeletons by Natural Material-Related Diversity-Oriented Synthesis

Abstract: Diversity-oriented synthesis (DOS) is an effective strategy for the quick creation of diverse and high three-dimensional compounds from simple starting materials. The selection of a starting material is the key to constructing useful, chemically diverse compound libraries for the development of new drugs. Here, we report a novel, general, and facile strategy for the creation of diverse compounds with high structural diversity from readily available natural products, such as zerumbone, as the synthetic starting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…These drugs were mainly discovered by constructing complex molecules from simple starting materials. [3,[33][34][35] Among these methodologies, is diversity-oriented synthesis (DOS) strategy developed by Schreiber and coworkers that is considered as one of the most powerful tools used to discover first-in-class lead drug candidates. It focuses on utilizing simple starting materials to construct a collection of small molecules possessing NP-like core structures, employing step-economic synthetic transformations (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These drugs were mainly discovered by constructing complex molecules from simple starting materials. [3,[33][34][35] Among these methodologies, is diversity-oriented synthesis (DOS) strategy developed by Schreiber and coworkers that is considered as one of the most powerful tools used to discover first-in-class lead drug candidates. It focuses on utilizing simple starting materials to construct a collection of small molecules possessing NP-like core structures, employing step-economic synthetic transformations (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…It focuses on utilizing simple starting materials to construct a collection of small molecules possessing NP-like core structures, employing step-economic synthetic transformations (Figure 2). [3,[34][35][36][37][38][39][40][41] Over the past two decades, DOS contributed to important discoveries in the DD field, such contributions included the introduction of privileged scaffolds or "chemical navigators" by Evans et al which widened the scope of DOS (Figure 3). [42][43][44][45] Moreover, to engage DOS libraries with biologically relevant chemical space, Waldmann et.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its ready availability and accessibility, zerumbone stands as a sustainable material for DOS [6,47] . Kitayama et al ., has published pioneering contributions in successful diversification of zerumbone, they reported six natural product‐like skeletons from zerumbone by applying the concept of DOS [50] . An allene type zerumbone derivative, 12‐membered ring, by a Doering‐LaFlamme allene method was believed to be an important building block that culminates in synthesis of BC ring of paclitaxel (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…[6,47] Kitayama et al, has published pioneering contributions in successful diversification of zerumbone, they reported six natural product-like skeletons from zerumbone by applying the concept of DOS. [50] An allene type zerumbone derivative, 12-membered ring, by a Doering-LaFlamme allene method was believed to be an important building block that culminates in synthesis of BC ring of paclitaxel (Scheme 2). [51] Structural modifications of zerumbone to diverse skeletal frameworks were achieved by various groups that include asymmetric epoxidation, [52] conjugate addition , [53][54][55] transannular cyclisation, [56] ring cleavage, [57,58] ring expansion reaction, [51] to name a few (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
“…Stabilization of oxocarbenium ion VI by Michael reaction at C10 with water affords compound 5a . Kitayama et al reported the synthesis of an oxabicyclo[5.4.1]­dodecane skeleton from zerumbone epoxide 1 , which serves as a supporting evidence for the mechanism and the stereochemical outcome at C2, C3 centers of 5a .…”
mentioning
confidence: 99%